AgriTech and Rural Transformation: Balancing Innovation Efficiency with Equity in Smallholder Farming Systems - Akhmad Syafi’i; Shobichah Shobichah; Ginna Novarianti Dwi Putri Pramesti (Advances In Social Humanities Research, 2026)
This study examines the role of Agricultural Technology (AgriTech) in driving rural transformation and evaluates the extent to which technological innovation can achieve a balance between efficiency and equity within smallholder farming systems. Employing a qualitative approach with a descriptive-exploratory design, data were collected through in-depth interviews, field observations, and document analysis involving 25 purposively selected respondents, comprising smallholder farmers, agricultural extension workers, AgriTech practitioners, and local government representatives. The findings reveal that AgriTech adoption significantly enhances productivity, optimizes resource utilization, and expands market access for smallholder farmers. Nevertheless, the overall adoption rate remains low due to structural constraints, including limited digital literacy, inadequate rural infrastructure, and prohibitive technology costs. Furthermore, the study identifies an emerging disparity in the distribution of technological benefits, indicating that without deliberate inclusive strategies, digital transformation may exacerbate existing socioeconomic inequalities in the agricultural sector. These findings underscore that sustainable agricultural transformation requires not only technological innovation, but also equitable access, enhanced human resource capacity, and evidence-based policy frameworks. This study contributes to the growing literature on AgriTech by integrating the dual dimensions of innovation efficiency and social equity, offering both theoretical enrichment and practical policy implications for inclusive agricultural development.